Development Of Clan Government In Ujan Mas, Muara Enim Regency 1975-1983 - Mareta Adelia; Yunani Yunani; Alian Alian (Criksetra: Jurnal Pendidikan Sejarah, 2019)
This research is entitled "The Development of the Marga Government in Ujan Mas District of Muara Enim Regency in 1983-2014". This study uses historical methods, using heuristic steps, criticism of sources, interpretations, and historiography carried out through the search of literature and interview research methods. This research discusses changes in the clan government system that turned into a system of village governance, this change along with the issuance of Law No. 5 of 1979 concerning regional government. So with the Act, South Sumatra issued a Guberner Decree Number 142 /KPTS / III / 1983 which stated that the clan government was abolished in South Sumatra. Changing the clan government system to village government also changed the structure of the clan government which was the lowest organization into a hamlet that was part of the previous clan and became the lowest governmental organization not the clan. This change also occurred in the structure of local government administration in the district Ujan Mas.